Implementation of the K-Nearest Neighbor Method to determine the Classification of the Study Program Operational Budget in Higher Education - Gufron; Bayu Surarso; Rahmat Gernowo (LPPM Universitas Duta Bangsa Surakarta, 2019)
Sultan Agung Islamic University annually designs operational costs for work programs in the study program and of course determines the amount of financial budget for the study program work program. K-Nearest Neighbor algorithm is needed to determine the required operational budget classification based on the number of active students, the number of financial admissions, the number of employees and the percentage of work program realization programs. The results of this study are to facilitate the leadership of higher education in the budget field to classify the amount of the budget required by study programs in the classification of up, or fixed. The purpose of this study is expected to facilitate the leadership of the financial budget department to classify the budget needed by the study program and as an awareness system in the work program of the study program with a classification value of 79.96% for the operational budget of the college study program.